L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost L’effet du compost de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia de l'insecte Hermetia IllucensIllucensIllucensIllucensIllucensIllucens (Diptera (Diptera(Diptera(Diptera(Diptera(Diptera Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture Stratiomyidae) dans la culture de poivronde poivron de poivronde poivronde poivronde poivronde poivronde - OULD ABBES, Tata Imene; BENMEHAL, Afaf (My University, 2023)
Excessive use of mineral fertilizers, especially those containing nitrogen, can lead to severe environmental issues such as water pollution from eutrophication and degradation of the ozone layer. These fertilizers can also deplete the soil by depriving it of essential organic materials. Despite these challenges, fertilization remains crucial for supporting agricultural yields and meeting the nutritional needs of plants. The aim of the study is to use the Black Soldier Fly (Hermetia illucens) for household waste management and its ability to transform these wastes into potential fertilizer for crops. This study demonstrated the effectiveness of the Black Soldier Fly in degrading household waste and chick feed. Notably, peppers fertilized with the exoskeletons of this fly showed superior growth compared to those planted in standard potting soil. Analyses revealed a variation in nitrogen content between 0.585 and 19, an increase in stem size from 26.75 to 39.833, and an increase in the number of leaves, ranging between 6.346 and 45.833. Regarding the composition of the peppers, those fed with fertilizer derived from the exoskeletons showed notable contents: 7.8% for dry matter, 0.467% for mineral matter, and 0.357% for proteins. Before the addition of the fertilizer, the soil had a pH of 7.8, a conductivity of 0.247, a calcium carbonate content of 16.56, and a phosphate content of 291 (P2O5). After fertilization, significant changes in soil characteristics were observed: the pH ranged between 8.33 and 8.385, conductivity reached 0.394, and there was a notable improvement in the organic composition of the soil.
Keywords: Black Soldier Fly; fertilization; chemical fertilizer; exoskeleton; chick feed; pepper cultivation